Corpo-fogo e deseducação artística: uma perspectiva do feminismo interseccional no entrelace das obras de Ana Mendieta, Marli Wunder e Tamires Neto - Silva Neto, Tamires da (2024)
This experimental writing-research is an attempt to establish possible dialogical paths between Fire-Bodies in works by artists who aim to de-educate sensibilities. Intending to allow some rupture in determining thoughts based on the works of Ana Mendieta, Marli Wunder and authors, we will seek to see the ambiguous ties that create bridges between nature, home, world in an attempt to understand the interrelational behind-the-scenes that seem contradictory and conflicting. How can we transgress ourselves by seeking other ways of existing through Body-art-fire-spark, understanding intersectional feminism as a strategy for miseducating sensibilities? Based on autobiographical narratives, in images-threadswords, discussed in meetings of the Trace research group and using cartography as a method, I present an exercise in fictional writing, of memories, affectations and feelings-images. As the condition of a woman's body also moves me angrily in search of ruptures in thoughtresearch-writing, one of the lenses we use to consciously see the world is through intersectional feminism because we understand that it is essential to talk about other crossings such as race and class. The research-image-works are intrinsically linked to the artists’ bodylife